Structure of rings with certain conditions on zero divisors - Hazar Abu-Khuzam; Adil Yaqub (International Journal of Mathematics and Mathematical Sciences)
Let R be a ring such that every zero divisor x is expressible as a sum of a nilpotent element and a potent element of R:x=a+b, where a is nilpotent, b is potent, and ab=ba. We call such a ring a D*-ring. We give the structure of periodic D*-ring, weakly periodic D*-ring, Artinian D*-ring, semiperfect D*-ring, and other classes of D*-ring.